Effect of seawater flow velocity in South Malang on the corrosion rate of low carbon steel with a corrosion coupon rack - Suprapto, Agus; Irwandi, Jul Viansyah Dwiki; Jumiadi, Jumiadi; Tsamroh, Dewi Izzatus (Jurnal Polimesin, 2024)
Corrosion is a phenomenon of damage to metal that can be influenced by several factors, including environmental factors, namely pH, humidity, temperature, and impurity factors. Corrosion that occurs due to the flow of a fluid is known as erosion corrosion. One type of metal that is susceptible to corrosion is carbon steel. Carbon steel material is very commonly used in the industrial world. An application of carbon steel is in piping systems that transport fluids; thus, fluid flow velocity affects the corrosion resistance of carbon steel. This research aimed to determine the effect of seawater flow on the corrosion rate of low carbon steel (ST 37) with variations in seawater velocity. This research is a type of laboratory-scale experimental research using coupon rack corrosion test equipment. The variations in seawater velocity used are 0 L/min, 15 L/min, 20 L/min, and 25 L/min. Observations of each experiment were carried out every 6 and 12 hours. The corrosion rate was analyzed using the weight loss method, namely by calculating the initial and final weight of the specimen before and after the experiment. The results show that increasing seawater flow velocity also increases the corrosion rate on steel specimens, with the lowest corrosion rate at 10.262 mpy on specimens with a variation of 0 L/min, while the highest corrosion rate is 48.743 mpy on specimens with a variation of 25 L/min. It can be concluded that the velocity of the fluid flow and the type of particles contained in the flow affect the rate of erosion-corrosion. The higher the fluid flow velocity and the more abrasive the particles contained in the flow, the faster the rate of erosion-corrosion.